Characteristics of Wet Noodles From Sago and Sweet Potato Starch with Mung Bean Flour Substitution - Shanti Fitriani; Yusmarini Yusmarini; Emma Riftyan; Yossie Kharisma Dewi; Ririn Puji Lestari; Tiyah Fadhilah (Food ScienTech Journal, 2024)
Sago starch and sweet potato starch are promising alternatives for wet noodle production due to their high amylose and amylopectin content, which contribute to desirable quality characteristics. This study was conducted to determine the effect of the ratio of starch (sago and sweet potato respectively) to mung bean flour on the physicochemical properties of wet noodles, as well as to obtain the best wet noodle formulation. The research was conducted experimentally using a completely randomized design with ten treatments and four replicates. The treatments involved varying ratios of starch to mung bean flour for sago starch-based noodles (SP1: 100:0, SP2: 80:20, SP3: 70:30, SP4: 60:40, SP5: 50:50) and sweet potato starch-based noodles (JP1: 100:0, JP2: 80:20, JP3: 70:30, JP4: 60:40, JP5: 50:50). Parameters measured for the starches included water holding capacity (WHC), swelling power, and solubility. Wet noodle parameters included moisture, ash, and protein content, elongation, water absorption, and sensory characteristics (color, aroma, taste, chewiness, and overall preference). Data were analyzed statistically using ANOVA and further evaluated with DMRT at a 5% significance level. Results showed that different ratios of sago or sweet potato starch and mung bean flour significantly affected all observed parameters. Among the treatments, JP4 (60:40) received the highest hedonic scores, indicating panelists’ preference for all sensory attributes, including color, aroma, taste, chewiness, and overall acceptability. This study demonstrates the potential of using sago starch and sweet potato starch with mung bean flour substitution to develop wet noodles that meet both sensory and nutritional quality standards.